Milk whey as a sustainable alternative growth supplement to fetal bovine serum in muscle cell culture - T.S. Sundaram; C. Giromini; R. Rebucci; D. Lanzoni; E. Petrosillo; A. Baldi; F. Cheli (Journal of Dairy Science)
ABSTRACT: In vitro meat cultivation, a cutting-edge innovation in food science, may represent a more sustainable and ethical source of animal proteins compared with conventionally grown meat. An important challenge for meat cultivation lies in eliminating the use of fetal bovine serum (FBS) in cell culture media due to ethical concerns. Milk whey is a nutrient-rich liquid portion of the milk, derived as a byproduct of dairy industry. Similar to FBS, whey contains proteins that are crucial for nutrition, cell adhesion, and biomolecular transport. In this study, we investigated whether whey proteins (WP) can replace FBS in supporting muscle cell cultivation, using the C2C12 myoblast model. Accordingly, under serum-free conditions, cells were treated with 2 WP mixtures, grouping high (β-LG 1.25%, α-LA 1.25%, BSA 1.25%) and low (β-LG 0.07%, α-LA 0.15%, BSA 0.15%) selected concentrations of individual proteins that positively affected cell growth in a preceding dose–response study. Cells cultured in only basal Dulbecco's Modified Eagle Medium were included as a negative control, and cells cultured in 10% FBS as a positive control. Cells were maintained in the treatment media for 48 h (d 1 and 2) to support myoblast proliferation. Subsequently, all the treatments were replaced with a standard low mitogenic 2% horse serum (HS) medium until full differentiation (d 6). The treatment effects on morphology, viability, and lactate dehydrogenase release were assessed after d 1, 2, and 6, respectively. The results showed that WP stimulated cell proliferation under serum-free culture conditions, similar to the FBS control, and subsequently facilitated myotube formation when the WP or FBS treatments were switched to HS medium. After differentiation, these cells also exhibited increased expression of cell differentiation markers such as creatine kinase and citrate synthase and underwent morphological changes from spindle-shaped cells to fused elongated myotubes, in contrast to the negative control. This study demonstrates that WP are a promising and sustainable alternative for considerably replacing FBS-based growth supplements for use in cultivated animal products.